2017
DOI: 10.11604/pamj.2017.26.134.7827
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram profile of uropathogens isolated at Bahir Dar Regional Research Laboratory Centre, Ethiopia

Abstract: IntroductionAntimicrobial resistance among bacteria that cause urinary tract infection (UTI) has been increasing since the introduction of chemotherapy. This study was aimed to assess the types of isolates from patients with UTI and to determine their current antimicrobial susceptibility profile.MethodsA record based retrospective analysis of bacterial uropathogens processed in the period of January 2012 to December 2014 at Bahir Dar Health Research Laboratory Center (BRHRLC) was determined. According to stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
26
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 7 publications
11
26
0
3
Order By: Relevance
“…This underscores the fact that many studies have reported highly resistant and have recommended the disbandment of its use as the drug of choice for empirical treatment of UTI management globally. For instance, high rate of resistance against Cotrimoxazole was reported by studies done in India, Brazil, and Iran (Prakash and Saxena, 2013;Jeevan and Zarrin, 2017;Peixoto De Miranda et al, 2014;Rocha et al, 2012;Aghazadeh et al, 2015) and also by other studies done in Ethiopia (Derbie et al, 2017). Nonetheless, reduced susceptibility of E. coli isolates from patients with UTI to Co-trimoxazole varying from (0.00% susceptibility) to (13.90% susceptibility) have been reported by other studies done in different part of Nigeria (Ochada et al, 2014;Oreh and Attama, 2013;Dada-Adegbola and Muili, 2010;Uwaezuoke and Ogbulie, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…This underscores the fact that many studies have reported highly resistant and have recommended the disbandment of its use as the drug of choice for empirical treatment of UTI management globally. For instance, high rate of resistance against Cotrimoxazole was reported by studies done in India, Brazil, and Iran (Prakash and Saxena, 2013;Jeevan and Zarrin, 2017;Peixoto De Miranda et al, 2014;Rocha et al, 2012;Aghazadeh et al, 2015) and also by other studies done in Ethiopia (Derbie et al, 2017). Nonetheless, reduced susceptibility of E. coli isolates from patients with UTI to Co-trimoxazole varying from (0.00% susceptibility) to (13.90% susceptibility) have been reported by other studies done in different part of Nigeria (Ochada et al, 2014;Oreh and Attama, 2013;Dada-Adegbola and Muili, 2010;Uwaezuoke and Ogbulie, 2006).…”
Section: Discussionmentioning
confidence: 89%
“…No presente estudo, a maioria das bactérias isoladas foi proveniente de pacientes do sexo feminino (54,7%), corroborando os achados de diversos estudos similares, e explicado anatomicamente. (5,6,(8)(9)(10)(11)(14)(15)(16)(17) A prevalência de identificação nas amostras foi de Klebsiella pneumoniae (18,0%), Escherichia coli (17,6%) e Pseudomonas aeruginosa (9,5%), sendo semelhante à prevalência reportada por Derbie et al, (16) Rezaee et al, (11) Gilani et al, (17) Bitencourt et al (5) e Yoon et al, (6) o que chama a atenção por serem bactérias Gram negativas com grande probabilidade de desenvolverem rapidamente mecanismos de resistência a múltiplos antibióticos. (12) É interessante observar que na maioria dos trabalhos referenciados encontra-se pelo menos um desses microrganismos mais prevalentes como agente principal de ITU, independente da população analisada, o que demonstra a ampla disseminação desses microrganismos.…”
Section: Discussionunclassified
“…(12) É interessante observar que na maioria dos trabalhos referenciados encontra-se pelo menos um desses microrganismos mais prevalentes como agente principal de ITU, independente da população analisada, o que demonstra a ampla disseminação desses microrganismos. (5,6,(8)(9)(10)(11)(14)(15)(16)(17) O coco Gram positivo mais isolado foi o Enterococcus faecalis, mesmo microrganismo descrito no estudo de Rezaee et al (11) e Yoon et al, (6) o que se torna coerente já que o público alvo de ambos também era de pacientes hospitalizados. Entretanto, Haque et al (14) e Reis et al (10) demonstraram como mais prevalente entre os cocos Gram positivos o Staphylococcus saprophyticus, apesar do primeiro trabalhar com amostras hospitalares.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…12,13,14 It is therefore important to determine the antibiotic sensitivity pattern in any particular community in order to select the best empiric antibiotic. It is also necessary to determine the sensitivity patterns of non-beta lactam antibiotics against ESBL and non-ESBL producers in order to prescribe appropriate empiric antibiotic/s.…”
mentioning
confidence: 99%